Infamy [compact disc, unabridged] - Tanenbaum, Robert (Tanenbaum, Robert. Butch Karp and Marlene Ciampi series., 2016)
Prosecutor Butch Karp and his wife, Marlene Ciampi, return to solve the suspicious murder of a US Army colonel and battle government corruption at the highest levels.